Sur les chemins de l'amitié : Beiträge zur französischen Literaturgeschiche. Freundesgabe für Dietmar Rieger. / c herausgegeben von Anna Isabell Worsdorfer, Kirsten Dickhaut, Walburga Hulk, Gabriele Vickerman-Ribemont, und Stephanie Wodianka - Dickhaut, Kirsten; Hülk, Walburga; Vickermann-Ribémont, Gabriele; Wodianka, Stephanie (Culturae / intermedialität und historische anthropologie., 2017)
"Il ne faut pas laisser croître l'herbe sur le chemin de l'amitié" - guided by the idea of the well-known French proverb, the contributors to this festival publication take the 75th birthday of Prof. Dr. Dr. hc Dietmar Rieger as an opportunity to The field in which they pursue the literary traces of "amitié" and discover new paths with contributions by Anne Amend-Söchting, Wolfgang Asholt, Michel Delon, is as stretched as the jubilee's Romance research interests. Kirsten Dickhaut, Frank-Rutger Hausmann, Hinrich Hudde, Walburga Hülk, Mario Mancini, Eva-Tabea Meineke, Fritz Nies, Bernard Ribémont, Jörn Steigerwald, Gabriele Vickermann-Ribémont, Stephanie Wodianka, Anna Isabell Wörsdörfer and Friedrich Wolficket.